1996
DOI: 10.1021/bi961931j
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin-Free Neuronal Nitric Oxide Synthase:  Evidence for Two Identical Highly Anticooperative Pteridine Binding Sites

Abstract: The properties of neuronal nitric oxide synthase containing one tetrahydrobiopterin (BH4) per dimer [nNOS(BH4+)] were compared to those of the BH4-free enzyme [nNOS(BH4-)]. The stimulation by BH4 of the formation of L-citrulline at the expense of H2O2 production unambiguously demonstrated that BH4 is essential in coupling reductive oxygen activation to Arg oxidation. The clear difference between the Stokes radii of nNOS(BH4-) and nNOS(BH4+) indicates that the introduction of one BH4 per dimer significantly cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
148
0
4

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(177 citation statements)
references
References 45 publications
25
148
0
4
Order By: Relevance
“…In contrast, the full inhibition of basal activity by the type II anti-pterins was not due to loss of endogenous H 4 Bip from NOS (90 Ϯ 7% of control, 100 M PHS-72). It is possible that type II anti-pterins can only bind to the unoccupied, low affinity pterin-binding site of the NOS dimer (37). Nevertheless, inhibition by PHS-72 was fully reversible and inhibition was partially competitive with respect to H 4 Bip (Fig.…”
Section: Anti-pterins a Novel Class Of Pterinmentioning
confidence: 97%
“…In contrast, the full inhibition of basal activity by the type II anti-pterins was not due to loss of endogenous H 4 Bip from NOS (90 Ϯ 7% of control, 100 M PHS-72). It is possible that type II anti-pterins can only bind to the unoccupied, low affinity pterin-binding site of the NOS dimer (37). Nevertheless, inhibition by PHS-72 was fully reversible and inhibition was partially competitive with respect to H 4 Bip (Fig.…”
Section: Anti-pterins a Novel Class Of Pterinmentioning
confidence: 97%
“…The reasons for this discrepancy are unclear but might reflect isoform differences or, alternatively, methodological differences, e.g. the use of H % Bip-free NOS and measurements under catalytic [40] compared with non-catalytic conditions used in radioligand binding assays [35][36][37][38][39]. There is therefore uncertainty about the functional significance of allosteric binding site interactions in regulating NOS activity and NO generation.…”
Section: Discussionmentioning
confidence: 99%
“…Allosteric modulation within the catalytic centre of NOS by H % Bip has also been reported [35][36][37][38][39][40]. In a radioligand binding study, Mayer and co-workers demonstrated a 6-fold increase in the affinity of NOS-I for [$H]H % Bip in the presence of -arginine [35].…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies revealed that, in addition to redox regulation, H R B also regulates the homodimeric conformation of all three isoforms of NOS. Each nNOS dimer has two identical, anticooperative, binding sites for both Arg and H R B [6]. Incubation with saturating concentrations of H R B induces substantial conformational changes in the homodimeric structure of nNOS, yielding a stabilized nNOS dimer with full NO-producing activity [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Each nNOS dimer has two identical, anticooperative, binding sites for both Arg and H R B [6]. Incubation with saturating concentrations of H R B induces substantial conformational changes in the homodimeric structure of nNOS, yielding a stabilized nNOS dimer with full NO-producing activity [6,7]. Stabilized nNOS dimer is resistant to 2% sodium dodecyl sulfate (SDS) at temperatures below 30³C, enabling separation of stabilized and non-stabilized nNOS dimers by means of low-temperature SDS-polyacrylamide gel electrophoresis (LT-SDS-PAGE) [7].…”
Section: Introductionmentioning
confidence: 99%